Foreign Direct Investment, Domestic Investment and Oil Price Nexus in Saudi Arabia - Mahmood, Haider; Alkhateeb, Tarek Tawfik Yousef (International Journal of Energy Economics and Policy, 2018)
Foreign Direct Investment (FDI) inflows are targeted by every country to give external support to the economy and to fill saving-investment gap as well. This paper highlights the contributing factors of FDI inflows in Saudi Arabia by using annual data of 1970-2015 and by applying Auto-Regressive Distributive Lag (ARDL) cointegration methodology. This paper finds that Oil Price (OP) and Financial Market Development (FMD) are positively affecting to the FDI inflows. But, increasing Domestic Investment (DI) is found responsible for decreasing FDI inflows. Therefore, domestic investment can be considered as substitute for FDI inflows. This research recommends the Saudi government to promote FMD to support FDI inflows in Saudi Arabia and to diversify from oil dependence. Keywords: FDI Inflows; Oil Price; Financial Market Development; Domestic Investment JEL Classifications: F21; F41; O16